Report on industrial attachment in collaboration with Janssen-Cilag - Huang, John Yong An. (2010)
This report is consisted of 11 chapters. The key focus of this report lies on the lessons and significance behind the work and projects done. Technical details will be elaborated in the appendices. A clear overview of the general marketing procedures in a pharmaceutical firm will be given in this report. These theoretical marketing procedures will be put into practice during a customer tender report in order for Janssen-Cilag to successfully win a medical tender from NKF. Market analysis is also an important aspect of the work scope for a marketer. An in-depth market analysis is carried out in Project Flow to evaluate the market interest level of a new drug in the statin market. A forecasting model is also being used in the report to demonstrate how a forecast model can be used to estimate the market interest for a product. In a corporate industry, business planning is an important event for the company as it will determine the budget allocated to the company in the upcoming financial year. This report will also explain the process of business planning in Janssen-Cilag and how data is being presented in the best interest of the company. The last few sections of the report explain the importance of product understanding and soft skills efficiency in the course of work.